Soil Test-Based Fertilizer Prescriptions under Integrated Plant Nutrient Management System for Garlic in an Inceptisol of Eastern Plain Zone of Uttar Pradesh - Y.V. Singh; S.K. Singh; P. Dey (Journal of the Indian Society of Soil Science, 2023)
A field experiment was conducted on an Inceptisol of Agricultural Research Farm, Banaras Hindu University, Varanasi, UP, India during rabi 2021-22 by using an integrated plant nutrient management system (IPNMS) based on STCR approach. The study aimed to develop fertilizer recommendation equations for the cultivation of garlic. Soil test data, bulb yield and nitrogen, phosphorus and potassium uptake by garlic crop were used for achieving four important basic parameters, viz., nutrients required to produce one quintal of garlic bulb (NR), contribution of nutrients from fertilizers (%CF), contribution of nutrients from soil (%CS) and contribution of nutrients from organic matter-FYM (%C-OM). It was found that 2.04, 0.34 and 1.57 kg of N, P2O5 and K2O were required to produce one quintal garlic bulb yield. The %CS, %CF and %C-OM were 17.8, 23.1 and 17.7 for N; 20.7, 12.5 and 37.9 for P2O5 and 4.5, 3.6 and 7.2 for K2O, respectively. By using these basic parameters, a ready reckoner of fertilizer doses was prepared for varying soil test values and desired yield targets of garlic bulb yield using NPK alone and NPK with FYM.